Electronic Batch Recording Solutions Introduction of an Evaluation Model for the Pharmaceutical Industry - Futschik, Monika (Springer Fachmedien Wiesbaden : Vieweg, 2018)
Monika Futschik introduces an evaluation model that allows a holistic assessment of the advantages and disadvantages of electronic batch recording solutions versus traditional paper batch ticket solutions. In comparison to former studies, this newly developed evaluation model considers the change management efforts and the financial investments required for system deployment. The model proves the overall performance value through the implementation of electronic batch recording solutions and supports decision-makers in finding the most effective solution. The development and effectiveness of this model is based on various surveys, expert interviews, a Delphi study as well as a case study with a real-life pharmaceutical company.The outcome of her research can be easily applied to other industries as well. Contents The Role of Batch Recording in Pharmaceutical Operations Characteristics for the Pharmaceutical Supply Chain Tiers Analysis of Generic Solution Types Design Guidelines of the Performance Evaluation Model Integration and Application of the Evaluation Model Target Groups Lecturers and students in computer science, operations and supply chain management Decision-makers and managers in pharmaceutical manufacturing, managers responsible for digitalization and industry 4.0 The Author Monika Futschik today works as head of finished goods packaging and operations support at a pharmaceutical company in Mannheim, Germany. During her PhD she analyzed various electronic batch recording solutions within the pharmaceutical industry. .